Effects of Ambient and Annealing Temperature in HfO2 Based RRAM Device Modeling and Circuit-Level Implementation. (1st February 2022) - Napolean, A.; Sivamangai, N. M.; Rajesh, S.; Naveenkumar, R.; Sharon, N.; Nithya, N.; Kamalnath, S.
Abstract : This article focuses on the relevance of the effect of ambient temperature and annealing in the context of compact modeling of metal oxide resistive random access memory (RRAM) devices. The ambient temperature affects the conduction characteristic of resistive switching memories, so it becomes an essential factor to include when adjusting the experimental data. Reported the fabricated results and memory switching parameters with the defined set (Vset) and reset (Vreset) transition voltages for the fabricated annealed HfO2 -based RRAM. Additionally, to illustrate the importance of this characteristic in the form of the I-V curve, the Stanford model (SFM) for RRAM devices is enhanced by incorporating the annealing temperature as an additional parameter in the script of the Verilog-A model. Stanford and modified Stanford model (MSFM) are analyzed at the device level using cadence circuit simulator and implemented in the nonvolatile memory circuit (3 *3 memory arrays). Results confirmed that the experimental switching voltages, Vset, Vreset are 1.7 V, −0.8 V. These values are well suited along the simulated MSFM switching voltages of, Vset, Vreset (1.8 V, −0.7 V). The mean error percentage of the MSF is 18.42%.